2012
DOI: 10.1080/15228916.2012.727756
|View full text |Cite
|
Sign up to set email alerts
|

Banking Consolidation in Nigeria, 2000–2010

Abstract: This study examines the Nigerian banking consolidation process using a dynamic panel for the period 2000-2010. The Arellano and Bond (1991) dynamic GMM approach is adopted to estimate a cost function taking into account the possible endogeneity of the covariates. The main finding is that the Nigerian banking sector has benefited from the consolidation process, and specifically that foreign ownership, mergers and acquisitions and bank size decrease costs.Directions for future research are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 71 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…In 2013, profitability decreased by 2%, which shows evidence of market congestion. Consolidation was adopted in 1970 in Nigeria (Barros and Caporale, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, profitability decreased by 2%, which shows evidence of market congestion. Consolidation was adopted in 1970 in Nigeria (Barros and Caporale, ).…”
Section: Resultsmentioning
confidence: 99%
“…The general conclusion is that Angolan banks are efficient and relatively homogeneous, yet face difficult problems (Barros and Caporale, ). The major policy implication of this study is that common policies are suitable for this relatively homogeneous banking market and benchmarking studies should be adopted on a regular basis to observe the evolution of Angolan banks over time.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The quest for maximum result within a minimum time led to the use of young staff (females in particular) as marketers to get customers to deposit money and promotion depended on the number (calculability) one attracts (Dumbili, 2013). As these processes yielded some positive results such as cost-efficiency (see Barros & Caporale, 2012), they also came with the irrationalities that often accompany any McDonaldized business (Ritzer, 2000). Some of the irrationalities are as follows: the increasing spending by customers due to multiple bank charges, myriad of techno-based crimes in the sector, job insecurities, and so on (Dumbili, 2013).…”
Section: Evidence Of the Mcdonaldization Process Of Nigerian Banksmentioning
confidence: 99%
“…To find out if Nigeria's banking sector has benefitted from consolidation through reduced costs and improved competition, Barros and Caporale (2012) developed a generalized method of moments (GMM) model. Using dynamic panel data for the period 2000 -2010, they found that the sector has benefitted from the consolidation process and specifically that foreign ownership, mergers and acquisitions and bank size decreased costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results they obtained seem to support the official position that M&A in the banking industry had promoted sustained competition and higher efficiency levels, resulting in a minimal reduction of interest rate spread. While the approach adopted by Okafor et al (2012) was robust, utilizing the strengths of the Herfindahl-Hirscman index, the model developed by Barros and Caporale (2012) had the capacity of allowing for dynamics in the dependent variable because of the inbuilt and plausible empirical assumption that the best performing banks were likely to remain so in the subsequently years. However, the two models were not specifically developed to estimate the impacts of M&A on the selected banks' operating/financial performance, as their main focus was on the bigger picture -competition and efficiency.…”
mentioning
confidence: 99%